Inducible nitric oxide synthase-expressing myeloid-derived suppressor cells regulated by interleukin 35 contribute to the pathogenesis of psoriasis - Zhang, Junfeng; Zhang, Yunsheng; Yang, Zhiya; Cheng, Dalei; Zhang, Hui; Wei, Li; Liu, Chen; Yan, Fenglian; Li, Chunxia; Dong, Guanjun; Wang, Changying; Shi, Dongmei; et al. (Frontiers in Immunology, 2023)
Although psoriasis is classified as a T cell-mediated inflammatory disease, the contribution of myeloid cells to the pathogenesis of psoriasis is not fully understood. In this study, we demonstrated a marked increase in the number of myeloid-derived suppressor cells in patients with psoriasis. Similar results were obtained in an imiquimod-induced psoriasis mouse model. Interleukin-35 (IL-35) reduced the total number of myeloid-derived suppressor cells and their subtypes in the spleen and psoriatic skin lesions, ameliorating psoriasis. IL-35 also reduced the expression of inducible nitric oxide synthase in myeloid-derived suppressor cells, although there was no difference in interleukin-10 levels. Adoptive transfer of myeloid-derived suppressor cells from imiquimod-challenged mice aggravated the disease and weakened the effect of IL-35. Myeloid-derived suppressor cells were isolated from inducible nitric oxide synthase knockout mice and transferred to wild-type mice. Mice with myeloid-derived suppressor cells isolated from inducible nitric oxide synthase knockout mice had milder disease than those with wild-type myeloid-derived suppressor cells. Furthermore, wild-type myeloid-derived suppressor cells reversed the effects of IL-35, while myeloid-derived suppressor cells isolated from inducible nitric oxide synthase knockout mice did not affect IL-35 treatment. In summary, in the development of psoriasis, MDSCs have an aggravating effect, mainly due to iNOS, and IL-35 may be a novel therapeutic strategy for patients with chronic psoriasis or other cutaneous inflammatory diseases.